Coarctation of aorta presenting as hypertensive encephalopathy in a young female - Sarthak Sharma; Ashutosh Pathak; Sourya Acharya; Samarth Shukla; Pankaj Banode (International Journal of Medical Research and Review, 2017)
Coarctation of Aorta (CoA) is a congenital cardiac defect which can present in adults. The usual presentation is hypertension. Though it has subtle clinical signs but they can go undetected if not sought for. One of the most catastrophic presentations can be severe hypertension with its complications. We report a case of a 40 year old female who presented to us with hypertensive encephalopathy and finally diagnosed as CoA